Investigating the Development and Psychometric Testing of the Information and Communication Technology Use Scale in Iranian Patients With Chronic Conditions - Sadat Izadi-Avanji, Fatemeh; Esmaeli, Tahereh (Journal of client-centered nursing care (Online), 2024)
Background: The high prevalence and associated costs of chronic diseases have challenged global community health. The use of information and communication technology offers patients and healthcare providers the ability to respond to healthcare needs. This study develops an information and communication technology use scale for patients with chronic diseases and evaluates its psychometric properties. Methods: This exploratory sequential mixed-method study was conducted in Kashan City, Iran from September 2020 to July 2021. In the qualitative phase, 18 patients with chronic conditions were recruited via the purposeful sampling method. The initial pool of 33 items was extracted in this phase. Psychometric evaluation of the scale was examined through face, content, and construct validity. The internal consistency of the scale was assessed with the Cronbach α and its stability was examined by the test re-test. To evaluate the scale’s construct validity, a cross-sectional study was performed with 300 patients referring to hospital wards and private centers that provide services to patients with chronic diseases. A sequential sampling method was used to select the subjects. The exploratory factor analysis was performed using principal component analysis and the varimax rotation method in the SPSS software, version 16. Results: The initial version of the scale consisted of 33 items. A total of 6 items were removed in the face and content validity evaluation phase. Factor analysis with the removal of 4 items resulted in the extraction of 4 factors that explained 67.45% of the variance in the total scale score. The Cronbach α coefficient and intra-class correlation coefficient were estimated at 0.93 and 0.88, respectively. Conclusion: The scale developed in this study is a valid and reliable tool for measuring formation and communication technology use (including its dimensions) in patients with chronic diseases.